1978
DOI: 10.1136/sti.54.6.403
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of chlamydial infection of the cervix.

Abstract: A rapid serodiagnostic test for the presumptive diagnosis of chlamydial infection of the cervix has been developed. The method used is based on the modified micro-immunofluorescence test using pooled chlamydial antigens and the detection of different immunoglobulin classes of chlamydial antibody in sera and cervical secretions. The presence of IgG chlamydial antibody at a level of 1/64, or IgM antibody at a level of 1/8 or greater, or both in sera and IgG or IgA antibody at a level of 1/8 or more or both in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

1982
1982
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 14 publications
1
10
1
Order By: Relevance
“…[5][6][7][8] In the study of Treharne et al 7 the authors focused on the sensitivity of the method. For cervical IgG titres of > 8 they found a sensitivity of 0-74 compared with 0-64 in our study and a PPV of 0-39 (26/66) for cervical IgG (our calculation) and in our study 0-18 for the pregnant group but 0-53 for the teenage group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] In the study of Treharne et al 7 the authors focused on the sensitivity of the method. For cervical IgG titres of > 8 they found a sensitivity of 0-74 compared with 0-64 in our study and a PPV of 0-39 (26/66) for cervical IgG (our calculation) and in our study 0-18 for the pregnant group but 0-53 for the teenage group.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and positive predictive value (PPV) have ranged from 0 64-100 and 0-26-0.78 respectively.' [5][6][7][8] The most useful attribute of a diagnostic test for the clinician is a high PPV as pointed out by Schacter et a18 who found a sensitivity of 1 00 but PPV of only 0.26 for cervical IgG in a high prevalence population (20% positive culture). None of the studies mentioned above has found that local antibodies safely predict a positive outcome of culture of a single cervical specimen.…”
mentioning
confidence: 99%
“…In addition to isolation of C. trachomatis in cell culture, immunofiuorescence direct staining of genital samples and enzyme-linked immunosorbent assay seem to be of much interest (2,6,15,18,29).…”
mentioning
confidence: 99%
“…No contamination from blood could be detected by hemoglobin analyses. By using a special method for separating the proteins from the mu cins in the cervical secretions we were able to quantify the protein content by the use of nephelometry [8], Other investigators have used cervical vaginal washings and cellulose sponges combined with immunofluorescence tests [1][2][3][4][5]. The methods used in this study design allow for higher recovery of proteins and less bias in interpre tations.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with Chlamydia trachomatis in the female genital tract has been shown to increase antibody contents in local secretions [1][2][3][4][5][6][7]. Quantification of the antibody content has been intricate because of the rheo logical properties of the mucins in the secretions.…”
Section: Introductionmentioning
confidence: 99%